(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the linguistic and cultural functions of numbers in English and Uzbek, offering a comparative analysis of their syntactic, semantic, and pragmatic roles. It delves into the complexities of numerical expressions and their use in communication, with an emphasis on the unique features of each language. Through an extensive set of examples, the study highlights both the similarities and differences in number usage, providing a rich and detailed discussion of their impact on linguistic structures.